OPTIMIZING WRITING INSTRUCTION THROUGH THE INTEGRATION OF CHATGPT AS AN INTERACTIVE LEARNING TOOL IN JUNIOR HIGH SCHOOLS - Ikhwan Abdillah; Ryan Purnomo; Achmad Wahyudi; Ganal Arief Rahmawan (STKIP AL HIKMAH SURABAYA, 2025)
This study aims to optimize the management of writing instruction in Junior High Schools (SMP) through the use of ChatGPT as an interactive, artificial intelligence (AI)-based medium. Writing skills, particularly in English, are an essential part of students' literacy development, supporting global communication skills, critical thinking, and academic achievement. Unfortunately, many junior high school students still face difficulties in expressing ideas in writing, constructing proper sentence structures, and using correct grammar. ChatGPT, as a generative AI model, offers a more adaptive and personalized learning approach. This technology allows students to interact directly with an intelligent system that can provide feedback on their writing, suggest improvements, and help enrich their ideas. This research adopts a true experimental approach with a pre-test post-test control group design involving two junior high schools in Sidoarjo Regency. One group of students used a ChatGPT-based interactive writing model (experimental group), while the other group used conventional methods (control group). The instruments used included observation, writing tests (pre-test and post-test), teacher interviews, student questionnaires, and learning documentation. Data analysis showed that the experimental group experienced a significantly greater improvement in writing ability compared to the control group. The average pre-test score of the experimental group was 63.5 and increased to 81.2 in the post-test (a 17.7-point gain), while the control group only improved from 64.1 to 71.3 (a 7.2-point gain). An independent t-test confirmed that this difference was statistically significant. Furthermore, based on the questionnaire, students reported that ChatGPT was very helpful in generating writing ideas (86%), correcting grammar (91%), increasing confidence (78%), and boosting enthusiasm for writing (84%). This study demonstrates that the use of ChatGPT can be an innovative solution for enhancing the management of writing instruction and improving literacy skills among junior high school students.